Um estudo sobre as especificidades dos/as educandos/as nas propostas pedagógicas de educação de jovens e adultos-EJA: tudo junto e misturado - Jerry Adriani da Silva (2010)
It was became common in the educational ambient affirming that the pedagogical propositions of the Adults and Young People Education has been organized to attend the basic necessity for the apprenticeships of the young people and adults and welcoming the educative specificities of their public. The present study looked for describing and analysing through observations, documental analysis and interviews if actually the students have been organized in the pedagogical propositions in the schools of Adults and Young People Education situated in municipal districts of Belo Horizonte metropolitan region (a municipal school, a state school, another of the FIEMG System). It was selected thirteen actors: seven sudents and six educators that they were chosen by their participations in social context and involviment in the activities and practices of the school. It was inquired for the students if they have been recognized in those propositions and how the elements that compose their individuality have been treated by the schools. The collected empiric data reveal that in most of time that the curriculum of the Adults and Young People Education silences the thematic like racism, sexism and homophobia and it doesnt consider the established relations between the poor young people and poor adults, laborious people, residents in the periphery. In a first moment, it has been showed the insertion of the researcher in the area of Adults and Young People Education and also a view of this educative modality. Furthermore, it has been delineated the methodologic course. The chapter two has an experiment to think how the role of diferences procedures in the context of the Adults and Young People Education. Four specificities of the students have been described and analysed (gender, sexuality, ethnical and racial relations and a religious dimension). In the next moment, its taken others specificities from subjects of Adults and Young People Education like objects of analysis (poorness, social vulnerable, periphery, age and generation diversity and world of working) that become linked with the basic necessity of the public apprenticeship, but they are not placed in evidence in the pedagogical propositions of the schools. In the chapter four has been approched the principles that base the Adults and Young People Education propositions, as well as the divergent and common points in those propositions: the time adequation, space, curricular organization and valuation, further on the view-point of students about those Adults and Young people Education propositions. At the final consideration, after retaking the basis and principles that sustain the field of Adults and Young people Education, it has looked for placing in evidence the subjects specificities that many times they dont have been approched in the analysed propositions.